Heroes, gods and guardians hilts and keris of Indonesia : Huntington Miller Collection - Carpenter, Bruce W. (Talisman Publishing, 2021)
Put together over a period of twenty years, the Huntington Miller Collection of Keris and Keris Hilts is a tour de force. The emphasis here is on the sculptural aesthetic and historical importance of this unique art form from throughout Indonesia-Java, Sumatra, Borneo, Bali, Lombok, Sulawesi-and beyond. It is a story that spans centuries and the rise and fall of countless kingdoms and polities. The hilts range from minimalistic forms to the abstract to opulent royal weapons beautifully crafted to project prestige and wealth. So, too, they carry with them the aura of mystery and magic of the exotic tropical islands of Southeast Asia, which captured the imagination of foreigners even before the beginning of the Age of Spices, when the perilous journey from Europe to Indonesia took a year to complete. With a terse and informative text written by Indonesian art expert, Bruce W. Carpenter, this is a cultural and artistic voyage that delights the eye and stimulates the mind.